Rare earth niobium potassium-based lead-free antiferroelectric ceramic material and preparation method and application thereof

By introducing different ion combinations into rare earth potassium niobium (K2RENb5O15)-based lead-free antiferroelectric ceramic materials, the antiferroelectric phase zone is solved, and the existing ceramic materials have limited energy storage capacity at room temperature is achieved, and high energy storage is achieved Ceramic materials of density and efficiency.

CN119462145APending Publication Date: 2025-02-18SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411420202.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing antiferroelectric energy storage ceramic materials have limited energy storage capacity at room temperature, and have problems such as limited solid solution sites, large AFE-FE phase transition hysteresis, early saturation polarization, low turning field, and low density.

Method used

Using rare earth potassium niobium (K2RENb5O15)-based lead-free antiferroelectric ceramic material, the antiferroelectric phase region is regulated by introducing different ion combinations at the A and B positions, so that the material has antiferroelectric characteristics at room temperature and improves its saturation. Polarization strength, energy storage density and energy storage efficiency.

Benefits of technology

Lead-free antiferroelectric ceramic materials with high saturation polarization strength, low residual polarization strength, and high energy storage density and energy storage efficiency at room temperature are realized, and are suitable for the field of dielectric energy storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462145A_ABST
    Figure CN119462145A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of functional ceramics, and particularly relates to a rare earth niobium potassium (K2RENb5O15)-based lead-free antiferroelectric ceramic material as well as a preparation method and application thereof. Specifically, the chemical composition of the KRN-based lead-free anti-ferroelectric ceramic material disclosed by the invention is K2 (NdxSm1-x) (TayNb1-y) 5O (15-2.5 mol% of MnCO3), wherein x is mole percent, and x is more than or equal to 0.7 and less than or equal to 0.9; y is mole percent, and y is more than or equal to 0.15 and less than or equal to 0.3. The KRN-based lead-free antiferroelectric ceramic material has the characteristics of high breakdown strength, high energy storage density and the like, and is suitable for preparation and application of a ceramic capacitor and a dielectric capacitor in a high-power pulse system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of functional ceramics, and specifically relates to a rare earth potassium niobium (K2RENb5O 15 )-based lead-free antiferroelectric ceramic material and its preparation method and application. Background Art

[0002] Energy storage components are important components of power devices and power electronic devices. On the one hand, in recent years, pulse power technology with high power as its prominent feature has been increasingly widely used in defense, nuclear physics, medical equipment and other fields. On the other hand, with the progress of the new energy revolution and the increasing attention to environmental protection, the power electronics industry represented by electric vehicle inverters has grown rapidly. This puts higher requirements on the performance and production capacity of energy storage components. Dielectric capacitors with higher energy storage density will undoubtedly greatly promote the large-scale integration of electronic power systems. Among them, ceramic dielectric capacitors have become one of the most critical components in pulse power devices due to their good mechanical properties and thermal stability. Lead-based antiferroelectric energy storage ceramics represented by PbZrO3-based ceramics have high energy storage density, but this system contains a large amount of toxic lead elements, which brings serious harm to the environment and human body during production, preparation, use and waste treatment. Therefore, the development of new lead-free antiferroelectric energy storage ceramics with excellent performance is a very critical technology.

[0003] Based on the above introduction, it is of great strategic significance to study energy storage ceramic capacitors. For the core dielectric materials in ceramic capacitors, antiferroelectric materials are expected to achieve high energy storage density. However, there are many problems with existing antiferroelectric materials, such as: limited solid solution sites, difficult to regulate; large AFE-FE phase transition hysteresis, low efficiency; early saturation polarization, low turning field, low density; small dielectric constant, etc. Therefore, K2ReNb5O with rich structural adjustability is a tungsten bronze structure. 15 The system has great research value. The phase transition hysteresis of the system is small, the dielectric constant is moderate, the overall structure density is low, and it has the potential to achieve ultra-high energy storage density and lightweight. However, the antiferroelectric phase region of the material is at high temperature, and the energy storage capacity of the material is limited at room temperature. Therefore, how to effectively achieve antiferroelectric properties at room temperature is still a hot and difficult research topic in this field. Summary of the invention

[0004] In view of the above technical problems, the present invention provides a rare earth potassium niobium (K2RENb5O 15 )-based lead-free antiferroelectric ceramic material and its preparation method and application. The ceramic material of the chemical composition of the present invention can observe the typical hysteresis loop waist phenomenon at room temperature, has antiferroelectric characteristics, and has high saturation polarization intensity, low residual polarization intensity, high energy storage density and energy storage efficiency, and is expected to be applied in the field of dielectric energy storage.

[0005] In a first aspect, the present invention provides a KRN-based lead-free antiferroelectric ceramic material. The chemical composition of the KRN-based lead-free antiferroelectric ceramic material is: K2(Nd x Sm 1-x )(Ta y Nb 1-y )5O 15 -2.5mol%MnCO3; wherein, x is a molar percentage, 0.7≤x≤0.9; and y is a molar percentage, 0.15≤y≤0.3.

[0006] Preferably, 0.2≤y≤0.3; more preferably, 0.2≤y≤0.25.

[0007] Preferably, the relative dielectric constant of the KRN-based lead-free antiferroelectric ceramic material at 25°C and 1kHz is 300-400, and the dielectric loss is less than 0.01; the energy storage density of the KRN-based lead-free antiferroelectric ceramic material at 25°C and 10Hz is 0.7-9J·cm -3 , the energy storage efficiency is 50-90%; preferably, the energy storage density of the KRN-based lead-free antiferroelectric ceramic material at 25°C and 10Hz is 4-9J·cm -3 , the energy storage efficiency is 70~90%.

[0008] In a second aspect, the present invention provides a method for preparing a KRN-based lead-free antiferroelectric ceramic material. The preparation method comprises the following steps: According to the stoichiometric ratio of the KRN-based lead-free antiferroelectric ceramic material, a K source, a Nd source, a Sm source, a Ta source, and a Nb source are mixed and calcined to obtain an early solid solution powder; Mixing the previous solid solution powder with a Mn source to obtain a final solid solution powder; The final solid solution powder is mixed with a binder and granulated, and then aged, formed and extruded to obtain a green blank; The green blank is sintered to obtain the KRN-based lead-free antiferroelectric ceramic material.

[0009] Preferably, the K source is K2CO3, the Nd source is Nd2O3, the Sm source is Sm2O3, the Ta source is Ta2O5, the Nb source is Nb2O5, and the Mn source is MnCO3.

[0010] Preferably, the calcination temperature is 1150° C. to 1200° C., and the calcination time is less than 24 hours; preferably, the calcination time is 3 to 5 hours.

[0011] Preferably, the binder is at least one of polyvinyl alcohol, polyethylene glycol, polystyrene and methyl cellulose; the added amount of the binder is 6wt.% to 8wt.% of the final solid solution powder.

[0012] Preferably, the aging temperature is room temperature, and the time is 18 to 26 hours, preferably 22 to 26 hours; the temperature of the plastic removal is 600°C to 850°C, and the time is 1 to 24 hours; preferably, the plastic removal time is 1 to 6 hours.

[0013] Preferably, the sintering temperature is 1250° C. to 1300° C., and the sintering time is less than 24 hours, preferably 2 to 4 hours.

[0014] In a third aspect, the present invention provides a ceramic component, which is made from the KRN-based lead-free antiferroelectric ceramic material. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 X-ray diffraction patterns of ceramic materials prepared in Examples 1 to 4 of the present invention; Figure 2 The surface microscopic morphology of the ceramic material prepared in Examples 1 to 4 of the present invention; Figure 3 The hysteresis loop diagram of the ceramic element formed by the ceramic material prepared by Examples 1 to 4 of the present invention; Figure 4 The polarization current curves of the ceramic components formed by the ceramic materials prepared by Examples 1 to 4 of the present invention. DETAILED DESCRIPTION

[0016] The present invention is further described by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0017] The technical purpose of the present invention is to provide a K2RENb5O2 material for energy storage having antiferroelectric properties at room temperature. 15 Lead-free antiferroelectric ceramic material and its preparation method and its application in the preparation of ceramic components.

[0018] The KRN group (K2RENb5O 15 The chemical composition of lead-free antiferroelectric ceramic materials is: K2(Nd x Sm 1-x )(Ta y Nb 1-y )5O 15-2.5mol%MnCO3. The present invention has been verified through theoretical research and experimental verification, and found that for the room temperature antiferroelectric regulation of KRN-based ceramics, the introduction of Ta at the B position can make the antiferroelectric phase region move to room temperature; at the same time, the A position selects ions with different ion radii to further regulate the antiferroelectric phase region. Moreover, through different ion pairs and B position regulation, KRN-based materials can exhibit antiferroelectric properties at room temperature.

[0019] Wherein, x is a molar percentage, 0.7≤x≤0.9. As an example, x is selected from 0.7 or 0.9.

[0020] Wherein, y is a molar percentage, 0.15≤y≤0.3. If y is too large, the material will enter the paraelectric phase at room temperature, the polarization intensity will be reduced, and it will be unfavorable to improve the energy storage performance; if y is too small, the material will not be in the antiferroelectric phase at room temperature, and the ferroelectric phase exhibited by the material at this time is also not conducive to energy storage. Preferably, 0.2≤y≤0.3. As an example, y is selected from 0.2 or 0.3.

[0021] In some embodiments, the chemical composition of the KRN-based lead-free antiferroelectric ceramic material is K2(Nd 0.9 Sm 0.1 )(Ta y Nb 1-y )5O 15 -2.5 mol% MnCO3. Wherein, y is a molar percentage, 0.15≤y≤0.3.

[0022] In some embodiments, the chemical composition of the KRN-based lead-free antiferroelectric ceramic material is K2(Nd 0.7 Sm 0.3 )(Ta y Nb 1-y )5O 15 -2.5 mol% MnCO3. Wherein, y is a molar percentage, 0.15≤y≤0.3.

[0023] The ceramic material with the chemical composition provided by the present invention can observe the typical hysteresis loop waist phenomenon at room temperature, has antiferroelectric characteristics, and has high saturation polarization intensity, low residual polarization intensity, high energy storage density and energy storage efficiency, and is expected to be applied to the field of dielectric energy storage.

[0024] In some technical solutions, the KRN-based lead-free antiferroelectric ceramic material of the present invention has a relative dielectric constant of 300-400 at 25°C and 1kHz, and a dielectric loss of less than 0.01 (preferably a dielectric loss of less than 0.005, and more preferably a dielectric loss of less than 0.003); the KRN-based lead-free antiferroelectric ceramic material has an energy storage density of 0.7-9 J·cm at 25°C and 10Hz. -3, the energy storage efficiency is 50-90%; preferably, the energy storage density of the KRN-based lead-free antiferroelectric ceramic material at 25°C and 10Hz is 4-9J·cm -3 , the energy storage efficiency is 70~90%.

[0025] The following is an exemplary description of the method for preparing the KRN-based lead-free antiferroelectric ceramic material of the present invention.

[0026] According to the stoichiometric ratio of the KRN-based lead-free antiferroelectric ceramic material, a K source, a Nd source, a Sm source, a Ta source and a Nb source are mixed and calcined to obtain a preliminary solid solution powder.

[0027] Each metal source can be selected as needed. As an example but not limited thereto, the K source is K2CO3, the Sm source is Sm2O3, the Nd source is Nd2O3, the Nb source is Nb2O5, and the Ta source is Ta2O5.

[0028] As an example, the K source, RE source (Nd source, Sm source), Ta source, and Nb source are mixed for the first time, dried for the first time, and sieved for the first time according to the chemical composition ratio of the KRN-based lead-free antiferroelectric ceramic material, and then calcined and cooled to room temperature in the furnace to obtain a ceramic preliminary solid solution powder.

[0029] The first mixing method can be ball milling. During the ball milling process, the mass ratio of raw material: grinding ball: alcohol can be controlled to be 1: (4-8): (0.8-1.3). The grinding ball can be a zirconia ball, a zirconia column, an agate ball, etc. The ball milling time can be adjusted as needed. For example, the ball milling time is 4 hours. The mesh size of the first sieving can be 20-80 meshes.

[0030] The calcination temperature may be 1150-1200° C. The calcination time is less than 24 hours. Preferably, the calcination time is 3-5 hours. This allows the synthesis reaction of the KRN ceramic to fully occur. For example, the temperature is raised to the calcination temperature at a heating rate of 2° C. / min.

[0031] The powder can also be briquette-pressed at 100-300 MPa after the first screening, and then the pressed block can be calcined for synthesis. At the same time, the block can be further crushed and sieved (for example, 20-80 mesh) after synthesis, thereby improving the efficiency of subsequent mixing processes such as ball milling and saving preparation time.

[0032] The solid solution powder of the previous stage is mixed with a Mn source to obtain a final solid solution powder. The Mn source is preferably MnCO3. The Mn source accounts for K2(Nd x Sm 1-x )(Ta y Nb 1-y )5O15 The molar percentage is 2.5%.

[0033] As an example, a Mn source is added to the ceramic preliminary solid solution powder according to the chemical composition ratio of the KRN-based lead-free antiferroelectric ceramic material, and a ceramic final solid solution powder is obtained through a second mixing, a second drying, and a second screening.

[0034] The second mixing method can be ball milling. In the ball milling process, the mass ratio of raw material: grinding ball: alcohol is controlled to be 1: (4-8): (0.6-1.2). The grinding ball can be a zirconia ball, a zirconia column, an agate ball, etc. The ball milling time can be adjusted as needed. For example, the ball milling time is 12 hours. The mesh size of the second sieving can be 20-80 meshes.

[0035] The final solid solution powder is mixed with a binder and granulated, and then aged, formed and extruded to obtain a green blank.

[0036] The binder includes but is not limited to at least one of polyvinyl alcohol, polyethylene glycol, polystyrene, and methyl cellulose. The binder can be prepared into a solution with a concentration of 6wt.% to 8wt.%. For example, the binder is prepared into a solution with water. The amount of the binder added can be 6wt.% to 8wt.% of the weight of the final ceramic solid solution powder.

[0037] Aging can make the binder more evenly distributed in the powder, which helps the powder to be better formed. In some embodiments, the aging temperature is room temperature (25° C.) and the time is 18 to 26 hours. Preferably, the aging time is 22 to 26 hours.

[0038] The molding may be performed by dry pressing, and the molding pressure may be 100-300 MPa.

[0039] The temperature of the plastic discharge is 600°C to 850°C (preferably 650°C to 850°C), and the heat preservation time is 1 to 24 hours (preferably 1 to 6 hours). For example, the temperature is raised to the plastic discharge temperature at a heating rate of no more than 2°C / min.

[0040] The green blank is sintered to obtain a KRN-based lead-free antiferroelectric ceramic material.

[0041] The sintering temperature may be 1250-1300°C. The sintering time is less than 24 hours. Preferably, the sintering time is 2-4 hours. This makes it easy to form porcelain without component segregation. The sintering atmosphere may be air. For example, the temperature is raised to the sintering temperature at a heating rate of 2°C / min.

[0042] The present invention also provides the use of the above-mentioned KRN-based lead-free antiferroelectric ceramic material in the preparation of ceramic components, which include but are not limited to ceramic capacitors, dielectric capacitors in high-power pulse systems, and the like.

[0043] As an example, the KRN-based lead-free antiferroelectric ceramic material is processed into a desired size, and after cleaning (e.g., ultrasonic cleaning), drying, silvering, and silver-sintering, a KRN-based antiferroelectric ceramic element can be obtained. The silver-sintering can be carried out by keeping the temperature at 600 to 900° C. for 10 to 30 minutes. The temperature can be raised to the silver-sintering temperature at a heating rate of no more than 2° C. / minute.

[0044] In summary, the KRN-based lead-free antiferroelectric ceramic material obtained by the present invention through component regulation has the characteristics of high withstand voltage, low residual polarization strength, high saturation polarization strength, high energy storage density, high energy storage efficiency, etc., and has a typical waist hysteresis loop characteristic at room temperature, and is suitable for the preparation of KRN-based lead-free antiferroelectric ceramic components such as ceramic capacitors and dielectric capacitors in high-power pulse systems. Moreover, the preparation process provided by the present invention is simple and suitable for large-scale preparation in industrial production.

[0045] The following examples are further listed to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0046] Example 1

[0047] KRN-based lead-free antiferroelectric ceramic materials (K2(Nd x Sm 1-x )(Ta y Nb 1-y )5O 15 -2.5mol%MnCO3, x=0.9, y=0.25) comprises the following steps:

[0048] (1) According to the chemical composition ratio, potassium carbonate with a purity of 99%, niobium pentoxide with a purity of 99.93%, tantalum pentoxide with a purity of 99.99%, neodymium trioxide with a purity of 99.99%, and samarium trioxide with a purity of 99.9% are weighed using an electronic balance (weighing to an accuracy of 0.001g). The weighed raw materials are mixed and placed in a nylon jar, anhydrous ethanol is added to the jar, and zirconia columns and zirconia balls of different sizes are used as media. The nylon jar is placed on a planetary ball mill and mixed for 4 hours. Among them, the mass ratio of zirconia columns with a diameter of 15 mm and a height of 15 mm: zirconia columns with a diameter of 7.5 mm and a height of 7.5 mm: zirconia balls with a diameter of 10 mm is 4:2:3. After the ball milling is completed, the material is poured out, dried in a baking oven, and then sieved with a 40-mesh nylon sieve. The sieved mixed powder was pressed into a cylindrical block with a size of 65 mm in diameter and 20 mm in height on a press, calcined at 1180° C. for 4 hours, and then crushed through a 40-mesh sieve to obtain a ceramic pre-solid solution powder.

[0049] (2) The obtained ceramic pre-solid solution powder is put into the nylon tank again, and manganese carbonate powder accounting for 2.5% of the molar ratio of the ceramic pre-solid solution powder is added, and anhydrous ethanol is added to the tank not higher than 2 / 3 of the tank height, and zirconium oxide columns and zirconium oxide balls of different sizes are continued to be used as the medium, and the nylon tank is placed on the planetary ball mill for mixing for 12 hours. Among them, the mass ratio of zirconium oxide columns with a diameter of 15 mm and a height of 15 mm: zirconium oxide columns with a diameter of 7.5 mm and a height of 7.5 mm: zirconium oxide balls with a diameter of 10 mm is 4:2:3. Then pour out the material, dry it in a baking oven, and sieve it with a 40-mesh nylon sieve to obtain the finely ground ceramic final solid solution powder.

[0050] (3) Adding a polyvinyl alcohol aqueous solution with a concentration of 7wt.% to the final ceramic solid solution powder, the amount of the polyvinyl alcohol aqueous solution added is 6% of the mass of the final ceramic solid solution powder, and then uniformly granulating, passing through a 40-mesh sieve, aging at room temperature (25°C, 24 hours), and compression molding to obtain a cylinder with a size of 13mm in diameter×1mm in height, and performing extrusion molding (600°C, 2 hours). The extrusion-molded body is sintered in an air atmosphere (1280°C, 4 hours), and naturally cooled to room temperature to obtain the KRN-based lead-free antiferroelectric ceramic material.

[0051] Example 2

[0052] The preparation method of the KRN-based lead-free antiferroelectric ceramic material in this embodiment is similar to that in Embodiment 1, the main difference is that the chemical formula of the KRN-based lead-free antiferroelectric ceramic material is K2(Nd x Sm 1-x )(Ta y Nb 1-y )5O 15-2.5 mol% MnCO3, x=0.9, y=0.20.

[0053] Example 3

[0054] The preparation method of the ceramic material in this embodiment refers to that in Embodiment 1, the main difference is that the chemical formula of the ceramic material is K2(Nd x Sm 1-x )(Ta y Nb 1-y )5O 15 -2.5 mol% MnCO3, x=0.7, y=0.15.

[0055] Example 4

[0056] The preparation method of the ceramic material in this embodiment refers to that in Embodiment 1, the main difference is that the chemical formula of the ceramic material is K2(Nd x Sm 1-x )(Ta y Nb 1-y )5O 15 -2.5 mol% MnCO3, x=0.7, y=0.25.

[0057] Figure 1 The X-ray diffraction diagrams of the ceramic materials prepared in Examples 1 to 4 of the present invention are shown in Figure 1. It can be seen that the KRN ceramics prepared in the present invention have no impurity phase.

[0058] Figure 2 The surface microscopic morphology of the ceramic materials prepared in Examples 1 to 4 of the present invention is shown in Figure 1. It can be seen that the KRN ceramic materials prepared in the present invention are sintered densely.

[0059] The energy storage and other related performance parameters of the KRN-based lead-free antiferroelectric ceramic material of the present invention are obtained by testing with the TF Analyser 2000 equipment of aixACCTSystems. The test conditions are: room temperature, 10Hz. The KRN-based lead-free antiferroelectric ceramic material is processed, cleaned, dried, and electroded to obtain a ceramic component. Specifically, the KRN-based lead-free antiferroelectric ceramic material is processed into a desired size, and the KRN-based antiferroelectric ceramic component is obtained by cleaning, drying, and sputtering. The prepared ceramic component is subjected to a unipolar hysteresis loop test at room temperature and 10Hz. Figure 3 The hysteresis loop comparison diagram of the ceramic components prepared in Examples 1 to 4 of the present invention shows that the energy storage density of the ceramic components increases continuously with the increase of the electric field. Figure 4 Polarization current curves of ceramic components formed by ceramic materials prepared by embodiments 1 to 4 of the present invention. The presence of the antiferroelectric phase can be determined by the presence of four current peaks in four quadrants of the polarization current curve or by observing the phase region through the dielectric temperature spectrum.

[0060] Table 1

[0061] Table 1 shows the parameters related to the energy storage performance of the KRN-based ceramics prepared in Examples 1 to 4. Figure 3-4 It can be seen that significant depolarization currents appear in Example 1 and Example 4, which are antiferroelectric polarization characteristics and have higher energy storage efficiency, indicating that the introduction of Ta can regulate the antiferroelectric characteristics and improve the breakdown field strength at the same time; while the depolarization current of Example 3 begins to appear when close to zero field, showing ferroelectric polarization characteristics, with relatively low energy storage efficiency; although the antiferroelectric polarization behavior of Example 2 is not obvious, the relaxation polarization process can also show a certain energy storage density and considerable energy storage efficiency. Compared with other embodiments, Examples 1 to 2 have higher energy storage efficiency and higher energy storage characteristics, and are suitable for application in pulse power capacitor technology. Moreover, it can also be found that with the increase of Ta content, the antiferroelectric characteristics of the system at room temperature first increase and then weaken, but when the Ta content reaches 0.3, the ceramic is in the phase region from antiferroelectric structure to paraelectric structure at room temperature; at the same time, with the increase of Ta content, its saturation polarization intensity gradually decreases, which indicates that with the increase of Ta content, its antiferroelectric phase region gradually moves to low temperature, and KRN-based ceramics change from antiferroelectric characteristics to paraelectric characteristics.

[0062] In summary, the KRN-based room-temperature antiferroelectric ceramics provided by the present invention utilize different combinations of ion radius sizes to regulate the antiferroelectric properties, especially by doping different A and B-site elements to make the KRN-based ceramics exhibit different degrees of antiferroelectric properties at room temperature, which greatly improves the energy storage performance of the KRN-based ceramics, and is suitable for the preparation and application of ceramic capacitors and dielectric capacitors in high-power pulse systems.

[0063] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A KRN-based lead-free antiferroelectric ceramic material, characterized in that: The chemical composition of the KRN-based lead-free antiferroelectric ceramic material is: K2(Nd x Sm 1-x )(Ta y Nb 1-y )5O 15 -2.5mol%MnCO3; wherein, x is a molar percentage, 0.7≤x≤0.9; and y is a molar percentage, 0.15≤y≤0.

3.

2. The KRN-based lead-free antiferroelectric ceramic material according to claim 1, characterized in that: 0.2≤y≤0.3; preferably, 0.2≤y≤0.

25.

3. The KRN-based lead-free antiferroelectric ceramic material according to claim 1 or 2, characterized in that: The relative dielectric constant of the KRN-based lead-free antiferroelectric ceramic material at 25°C and 1kHz is 300-400, and the dielectric loss is less than 0.01; the energy storage density of the KRN-based lead-free antiferroelectric ceramic material at 25°C and 10Hz is 0.7-9J·cm -3 , the energy storage efficiency is 50-90%; preferably, the energy storage density of the KRN-based lead-free antiferroelectric ceramic material at 25°C and 10Hz is 4-9J·cm -3 , the energy storage efficiency is 70~90%.

4. A method for preparing a KRN-based lead-free antiferroelectric ceramic material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: According to the stoichiometric ratio of the KRN-based lead-free antiferroelectric ceramic material, a K source, a Nd source, a Sm source, a Ta source, and a Nb source are mixed and calcined to obtain an early solid solution powder; Mixing the previous solid solution powder with a Mn source to obtain a final solid solution powder; The final solid solution powder is mixed with a binder and granulated, and then aged, formed and extruded to obtain a green blank; The green blank is sintered to obtain a KRN-based lead-free antiferroelectric ceramic material.

5. The preparation method according to claim 4, characterized in that: The K source is K2CO3, the Nd source is Nd2O3, the Sm source is Sm2O3, the Ta source is Ta2O5, the Nb source is Nb2O5, and the Mn source is MnCO3.

6. The preparation method according to claim 4 or 5, characterized in that: The calcination temperature is 1150° C. to 1200° C., and the calcination time is less than 24 hours; preferably, the calcination time is 3 to 5 hours.

7. The preparation method according to any one of claims 4 to 6, characterized in that: The binder is at least one of polyvinyl alcohol, polyethylene glycol, polystyrene and methyl cellulose; the amount of the binder added is 6wt.% to 8wt.% of the final solid solution powder.

8. The preparation method according to any one of claims 4 to 7, characterized in that: The aging temperature is room temperature, and the time is 18 to 26 hours, preferably 22 to 26 hours; the temperature of the plastic removal is 600° C. to 850° C., and the time is 1 to 24 hours; preferably, the plastic removal time is 1 to 6 hours.

9. The preparation method according to any one of claims 4 to 8, characterized in that: The sintering temperature is 1250° C. to 1300° C., and the sintering time is less than 24 hours, preferably 2 to 4 hours.

10. A ceramic component, characterized in that: The ceramic component is made of the KRN-based lead-free antiferroelectric ceramic material according to any one of claims 1 to 3.